Employment Rights on Transfers of Undertakings in the United Kingdom - George-Dian Balan (CES Working Papers, 2009)
In April 2006, in the UK, came into force new rules relating to the obligations incumbent upon business owners if they pursue their alienation. These regulations come to meet several Europeandirective which seeks to ensure employees' rights and prevent any abuses. In this respect, the main novelty lies in the stressed placed on the right to information and consultation, their failure to attract the party at fault liability and corresponding sanctions.
Keywords: 330; employment rights; company law; United Kingdom; business; regulation